Administrative Law In The Common Law Countries: Recent Developments And Future Trends - Jain, M.P. (Journal of Malaysian and Comparative Law, 1983)
Administrative law represents a major growth area in the present-day common-law legal world. Gone are the days, when, under the influence of Dicey's formulation on Rule of Law, Administrative Law was looked down by common-lawyers with derision, as 'continential jargon', as mimical to rule of law, because they had a distorted view of Administrative Law as something sactioning government arbitrariness and as favouring the government against the individual.